Maintenance and preservation of viable sexually-reproducing yeast cells for high school and college biology laboratory classes - Octaviano, Lorena P. (Ribas) 1930-
A quantitative study on the viability of sexually reproducing yeast cells grown in various conditions led to a simple method of maintaining and preserving yeast cultures that can easily be available when needed for use in high school and college laboratory classes. This method has been proven to be successful in the preservation and extension of storage life of yeast cultures.